2023
DOI: 10.3389/fbioe.2023.1243856
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production from alkali-pretreated rice straw: effects on fermentation yield, structural characterization, and ethanol analysis

Reema Ningthoujam,
Pankaj Jangid,
Virendra Kumar Yadav
et al.

Abstract: Current ethanol production technology has a dire need for efficient conversion of lignocellulosic biomass to fermentable sugars. The conversion requires pretreatment of the biomass, one of the most expensive steps, and thus it is quite necessary to identify the most cost-effective and high-efficiency conversion method. In this study, rice straw (RS) biomass was pretreated using 4% NaOH alkali, soaked for 4 h, and autoclaved for 30 min. The structural and morphological changes were examined using Fourier transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Several studies on the production of bioethanol from lignocellulose have been reported. For instance, bioethanol (214.5 g•L −1 ) was produced from alkali-pretreated rice straw within seven days [158], while 25.3 g•L −1 of ethanol was produced from rice straw [159]. Table 3 presents several studies on the concentrations, yield, and productivity of bioethanol from lignocellulose.…”
Section: Alcoholsmentioning
confidence: 99%
“…Several studies on the production of bioethanol from lignocellulose have been reported. For instance, bioethanol (214.5 g•L −1 ) was produced from alkali-pretreated rice straw within seven days [158], while 25.3 g•L −1 of ethanol was produced from rice straw [159]. Table 3 presents several studies on the concentrations, yield, and productivity of bioethanol from lignocellulose.…”
Section: Alcoholsmentioning
confidence: 99%